2009
DOI: 10.1002/app.30060
|View full text |Cite
|
Sign up to set email alerts
|

Novel aluminum phosphate/cyanate ester composites: Thermodegradation behaviors and kinetic analyses

Abstract: Thermodegradation behaviors of novel aluminum phosphate/cyanate ester (AlPO 4 (KH550)/CE) composites were studied in detail. Results show that thermodegradation behaviors and kinetic parameters of AlPO 4 (KH550)/CE composites are greatly dependent on the AlPO 4 (KH550) loading. The addition of AlPO 4 (KH550) into CE resin changes the thermodegradation mechanism (mainly at the temperature lower than 450 C) and degradation process from two steps to three steps. Comparing with CE resin, AlPO 4 (KH550)/CE composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Huang's and Deng's associates pointed out that silica/AP and organosilicon/AP composites had good thermal stability. Our group found that cyanate ester (CE)/AP composites have much higher char yield ( Y c ) at high temperature than CE resin, and the experimental Y c values of the composites are higher than the value calculated using the “mixture rule” …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Huang's and Deng's associates pointed out that silica/AP and organosilicon/AP composites had good thermal stability. Our group found that cyanate ester (CE)/AP composites have much higher char yield ( Y c ) at high temperature than CE resin, and the experimental Y c values of the composites are higher than the value calculated using the “mixture rule” …”
Section: Introductionmentioning
confidence: 91%
“…Our group found that cyanate ester (CE)/AP composites have much higher char yield (Y c ) at high temperature than CE resin, and the experimental Y c values of the composites are higher than the value calculated using the "mixture rule". 24 Above researches have proved that AP has an obvious effect on improving the thermal stability of polymers, which provides a possibility for getting good flame retardance 25,26 ; however, this is not an inevitable trend. 27 Considering the importance and wide application as well as the nontoxicity, it is interesting to evaluate the flame retarding ability of AP.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development and wide applications of microwave heating technique in industrial field, the ideal wave‐transparent composite should not only possess ultrahigh mechanical strength, admirable thermal stability, and low dielectric constant but also excellent flexibility as well as good processability . Aluminum phosphate (AlPO 4 ) is a representative wave‐transmitting material, which has been extensively utilized in national defense, aviation aerospace, transportation, and other areas due to its high temperature resistance property and outstanding dielectric performance . However, the great brittleness, poor wear resistance, and complicated manufacturing process of this material have imposed restrictions on its practical applications as structural and functional composites.…”
Section: Introductionmentioning
confidence: 99%